Academic Well-Being in Students with Physical-Motor Disabilities: Examining the Mediating Role of School Belonging, Self-Compassion, and Academic Self-Efficacy - Maryam Ataei Nasab; Sahar Safarzadeh; Marzieh Talebzadeh Shoushtari (Shiraz University of Medical Sciences, 2023)
Background: Paying attention to well-being in educational contexts is essential in evaluating educational systems' health and dynamics. This research investigated the mediating role of academic self-efficacy in the correlation between school belonging and self-compassion in students with physical-motor disabilities.Methods: This correlational study employed structural equation modeling as the analytical approach. The statistical population for this study comprised all 12-18-year-old students with physical-motor disabilities in Ahvaz, Iran in 2022. The convenience sampling method was employed to select 282 students with physical-motor disabilities as participants. To collect data, the Academic Well-Being Questionnaire (AWQ), Sense of School Belonging Questionnaire, Self-Compassion Questionnaire-Long Form (SCS-LF), and Students' Academic Self-Efficacy Questionnaire (SASEQ) were used. The proposed model was evaluated using structural equation modeling in SPSS version 27 and AMOS version 24.Results: The mean and standard deviation of academic well-being, school belonging, self-compassion, and academic self-efficacy were 120.79±23.62, 66.48±19.46, 75.45±20.33, and 98.46±42.53, respectively. The findings revealed significant correlations between academic well-being and all direct paths except school belonging (P=0.001). Furthermore, the indirect paths of school belonging and self-compassion exhibited significant associations with academic well-being, mediated through the role of academic self-efficacy (P=0.001). Moreover, the model fit criteria, including comparative fit index (CFI) and root mean square error of approximation (RMSEA), were 0.98 and 0.04, respectively.Conclusion: Based on the results, the modified and final model of the study demonstrated a strong fit with the data. This model serves to identify practical factors contributing to the academic well-being of adolescents with physical-motor disabilities. Holding educational workshops to enhance school belonging and self-compassion in these students can improve their academic self-efficacy and overall well-being.